Overlap of highly FDG-avid and FMISO hypoxic tumor subvolumes in patients with head and neck cancer. (2nd November 2017) - Mönnich, David; Thorwarth, Daniela; Leibfarth, Sara; Pfannenberg, Christina; Reischl, Gerald; Mauz, Paul-Stefan; Nikolaou, Konstantin; la Fougère, Christian; Zips, Daniel; Welz, Stefan
Abstract: Background: PET imaging may be used to personalize radiotherapy (RT) by identifying radioresistant tumor subvolumes for RT dose escalation. Using the tracers [ 18 F]-fluorodeoxyglucose (FDG) and [ 18 F]-fluoromisonidazole (FMISO), different aspects of tumor biology can be visualized. FDG depicts various biological aspects, e.g., proliferation, glycolysis and hypoxia, while FMISO is more hypoxia specific. In this study, we analyzed size and overlap of volumes based on the two markers for head-and-neck cancer patients (HNSCC). Material and methods: Twenty five HNSCC patients underwent a CT scan, as well as FDG and dynamic FMISO PET/CT prior to definitive radio-chemotherapy in a prospective FMISO dose escalation study. Three PET-based subvolumes of the primary tumor (GTVprim ) were segmented: a highly FDG-avid volume V FDG, a hypoxic volume on the static FMISO image acquired four hours post tracer injection ( V H ) and a retention/perfusion volume ( V M ) using pharmacokinetic modeling of dynamic FMISO data. Absolute volumes, overlaps and distances to agreement (DTA) were evaluated. Results: Sizes of PET-based volumes and the GTVprim are significantly different (GTVprim > V FDG > V H > V M ; p < .05). V H is covered by V FDG or DTAs are small (mean coverage 74.4%, mean DTA 1.4 mm). Coverage of V M is less pronounced. With respect to V FDG and V H, the mean coverage is 48.7% and 43.1% and the mean DTA is 5.3 mm and 6.3 mm, respectively. For two patients, DTAs were larger than 2 cm. Conclusions: Hypoxic subvolumes from static PET imaging are typically covered by or in close proximity to highly FDG-avid subvolumes. Therefore, dose escalation to FDG positive subvolumes should cover the static hypoxic subvolumes in most patients, with the disadvantage of larger volumes, resulting in a higher risk of dose-limiting toxicity. Coverage of subvolumes from dynamic FMISO PET is less pronounced. Further studies are needed to explore the relevance of mismatches in functional imaging.